Pigs in Space:Is Miss Piggy Going in for Final Landing? A Statistical Analysis of the game Pass the Pigs® - Niklas Karlsson; Nicklas Pettersson (Örebro University School of Business, 2020)
Abstract The game Pass the Pigs® offers students in statistics to practice a lot of statistical concepts and methods in a coherent way. In this paper a probability model is derived based on assumptions of the data generating process. A previously suggested strategy of maximizing the expected score in each round is adapted to the model. Adopting this strategy requires estimating the score of accumulated points, where to stop rolling the pigs and pass them on to the next player, as a function of unknown parameters in the model. Point and interval estimators for the mentioned accumulated score are derived using the maximum likelihood method as well as the Delta method and Bootstrap methods. Data from an experiment is used to testing model assumptions and to get point and interval estimates.
Keywords: A22; A23; 330; Pigs; Game; Strategy; Delta Method; Bootstrap